Obtención de papel artesanal a partir de afrecho de malta proporcionado por la empresa Merak Colombia (2022)
The main objective of this degree work is to demonstrate that artisanal paper can be obtained from the malt bran provided by the company Merak Colombia through the pulping technique to obtain the cellulose present in the biomass. Before extracting cellulose from the bran, a fiber characterization was made in which the content of cellulose, lignin and hemicellulose was determined, likewise by means of the ASTM 871 and ASTM E1755-01 standards, the percentages of humidity and ash were calculated, and to Based on these results, the physicochemical composition of the malt provided by the company was identified, where 63.6% refers to the fiber content, 3.17% to ashes and the rest to proteins, vitamins and other components present in the biomass.